Impact of the COVID-19 pandemic on the homeless: results from a retrospective closed cohort in France (March–May 2020). (October 2021) - Husain, Maya; Rachline, Anne; Cousien, Anthony; Rolland, Simon; Rouzaud, Claire; Ferre, Valentine Marie; Gomez, Maria Vargas; Le Teurnier, Maï; Wicky-Thisse, Marie; Descamps, Diane; Yazdanpanah, Yazdan; Charpentier, Charlotte; et al.
Abstract: Objectives: To evaluate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, hospitalization and fatality rates in residents of homeless shelters run by Samusocial of Paris. Methods: We conducted a retrospective serological study between July and August 2020 on all residents and staff members of three homeless shelters run by Samusocial of Paris: two centres providing healthcare accommodation (HCA) and one a women's dormitory. We included all adults present in the shelters or who died of a proven SARS-CoV-2 infection during the first wave (March–May). SARS-CoV-2 antibodies were detected in serum samples using the SARS-CoV-2 IgG Architect (Abbott) test. Any participant with a positive PCR or serology was defined as a confirmed SARS-CoV-2 case. Results: We included 100 residents and 83 staff members. The confirmed SARS-CoV-2 rate by PCR or serology was 72/100 (72.0%) for residents and 17/83 (20.5%) for staff members. Women accommodated in the dormitory had the highest infection rate (90.6%). The hospitalization rate in residents was 17/72 (23.6%) and the death rate 4/72 (5.6%). All hospitalizations and deaths occurred among HCA residents. Among the residents of HCA shelters, 34/68 (50%) presented at least two comorbidity factors associated with being at high risk for severe SARS-CoV-2 infection. Conclusion: The SARS-CoV-2 infection rate was high in residents of these homeless shelters (10.6% seroprevalence in the Île-de-France region during the first wave). Severe SARS-CoV-2 infection was highly associated with the prevalence of comorbidities. This population should be considered as a priority in vaccination campaigns and in access to individual housing units when at risk.